PARENTS INVOLVEMENT IN IMPROVING CHARACTER OF CHILDREN THROUGH MATHEMATICS LEARNING - Husen, Sabaruddin Dahlan; Mansor, Rosnidar (SCAD Independent, 2018)
The aim of this paper is to discuss parental involvement to the development of children character in mathematics learning. Parents are very important in improving children character by spending more time at home together, awareness and concern of parents are very influential towards the formation of character and academic performance of children. Mathematics education can be seen as a situation or the nature or even the value of synergies with character development. The achievements of pupils in mathematics and their participation to a higher level in mathematics are a reflection of the attitudes and aspirations of their parents. This study discusses parents? involvement in improving the character of children through mathematical learning in the elementary school. This study describes the parent's knowledge and their character education, the concern towards their child's math skills, the difficulties of children in mathematics and the cooperation of the school and parents in improving the character of children at the elementary school.